Evaluation of MINTREX® Manganese as a Source of Manganese for Young Broilers - Yan, F.; Waldroup, P.W. (International Journal of Poultry Science, 2006)
The study was conducted to evaluate the relative bioavailability of MINTREX® Mn, an organic source of trace minerals, compared to reagent grade Mn sulfate and reagent grade Mn monoxide in diets for young broiler chicks. Nutritionally complete diets were formulated based on nutrient specifications of top broiler producers. Each of the Mn sources was added at 0, 100, 200, 400, 600, and 800 mg/kg. Diets were adjusted for the amount of 2-hydroxy-4 (methylthio) butanoic acid added from the MINTREX® Mn. All diets were fortified with 50 mg/kg Fe from ferrous sulfate, 100 mg/kg Zn from zinc sulfate, and 10 mg/kg Cu from copper sulfate. Diets were fed in mash form. Five male chicks (Cobb 500) were placed in each of 96 pens in battery brooders; six pens were assigned to each dietary treatment. Diets were fed from 1 to 20 d at which time body weight and feed consumption were determined and birds killed by CO2 inhalation. Tibias of all surviving birds, grouped by pen, were analyzed for bone ash and Mn content. There were no significant differences among treatments for body weight, feed conversion, feed intake, mortality, or tibia ash. Significant differences in tibia Mn content were observed among source and level of Mn. Slope-ratio analysis of the response to the various products indicated that birds fed MINTREX® Mn had 15.81% higher levels of tibia Mn than those fed the sulfate form and 53.89% higher levels of tibia Mn than those fed the oxide form, indicating greater biological availability of the Mn from the MINTREX® Mn than provided by commonly used inorganic forms of Mn.